Instrumentation Of The Abstinence's Likelihood Scale In Drug Addiction (ALSDA- ACREDA) - Amin Al Haadi Shafie; Hishamuddin Abdul Wahab; Mohd Khairul Anuar Rahimi; Nurul Ashikin Ahmat Miskam; Haniza Rais3 (Ashdin Publishing, 2024)
Volume 11, Issue 2